2008
DOI: 10.3746/jkfn.2008.37.5.578
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Related Dietary Behaviors and Sodium Intakes of University Students in Gyeonggi-do

Abstract: The objective of this study was to evaluate associations of dietary sodium (Na) intake with salt-related dietary behaviors of 218 university students (95 men; 123 women) living in Gyeonggi area. Dish frequency questionnaire (DFQ) was used to identify salt-related dietary behaviors and to determine Na intakes. In men, systolic & diastolic blood pressures, Na intakes and DFQ-15 scores were significantly higher than in women. High-salt intake group (HS), classified by DFQ-15, had higher scores of high-salt dietar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Without objective measures of sodium intake, either by dietary assessment or 24-hour urine collection, we cannot confirm the actual sodium intake level among participants. Previous studies with limited participants have confirmed a correlation between eating behaviors and actual sodium intake [ 16 , 17 ]. Yet, future research is needed to confirm the actual sodium intake levels and their associations with various psychosocial factors using nationally representative samples.…”
Section: Discussionmentioning
confidence: 76%
“…Without objective measures of sodium intake, either by dietary assessment or 24-hour urine collection, we cannot confirm the actual sodium intake level among participants. Previous studies with limited participants have confirmed a correlation between eating behaviors and actual sodium intake [ 16 , 17 ]. Yet, future research is needed to confirm the actual sodium intake levels and their associations with various psychosocial factors using nationally representative samples.…”
Section: Discussionmentioning
confidence: 76%
“…Sino-Japanese group , . (Lee et al, 2012;Lee et al, 2011), (Kang et al, 2013) ) Choi et al, 2009 (hypernatremia) (Jung and Shim, 2008;Kim, 2006).…”
mentioning
confidence: 99%
“…, 심혈관질환, 뇌혈관질환, 위암 (Lee et al, 2011), 골다공증(Bae & Yeon 2011) 및 비만 (Han et al, 2010) (Yon et al, 2011). Park et al(2008) (Kim et al, 2009b;Lee et al, 2010;Kim et al, 2011)과 연령별 나트륨 섭취량 및 관련 식품 섭취패턴 분석 (Chung & Shim, 2008;Hwang, 2012;Jang et al, 2009;Lee et al, 2010;Moon et al, 2009;Park et al, 2008;Shin et al, 2010;Yon et al, 2011), 나트륨 저감화를 위한 교육자료 개발 및 영양교육 효과 (Choi et al, 2009;Kim et al, 2009a;Kim et al, 2010;Shin et al, 2008) 등이 있다. Kim et al(2012) (Jo, 2000).…”
unclassified